2010
DOI: 10.1111/j.1651-2227.2010.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing assessment during oxygen administration in ventilated preterm infants

Abstract: Aim:  To document nurses’ opinions about their assessments of oxygen requirements in ventilated preterm infants receiving oxygen supplementation. Methods:  Survey design with descriptive statistics. The sample consisted of 111 nurses employed in clinical positions in neonatal intensive care units within Norway’s five regional hospitals. The questionnaire included questions about physiological and clinical observations used when assessing oxygen administration in ventilated preterm infants. Results:  A major fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…This may be due to nurses known the applicable methods in wards not all type may be used and they didn't updated their knowledge regarding oxygen methods. This result goes in the same direction with Solberg et al (2011) in studying nursing assessment during oxygen administration in ventilated infants, who found that the nurses" assessments when adjusting oxygen levels…”
Section: Discussionsupporting
confidence: 63%
“…This may be due to nurses known the applicable methods in wards not all type may be used and they didn't updated their knowledge regarding oxygen methods. This result goes in the same direction with Solberg et al (2011) in studying nursing assessment during oxygen administration in ventilated infants, who found that the nurses" assessments when adjusting oxygen levels…”
Section: Discussionsupporting
confidence: 63%
“…During a 7‐month period, 833 h of monitored parameters and video recordings were collected. In total, 12 patients (Table S1 in supporting information) were included with a median (range) GA of 26 2 / 7 (24 2 / 7 –28) weeks, BW of 760 (545–935) g and PNA of 4 (2–12) days. Recruitment failed in 46 patients because they did not need supplemental oxygen therapy in the first 2 weeks of life (27), parental refusal (8), imminent death (6) or the experimental set‐up was unavailable (5).…”
Section: Resultsmentioning
confidence: 99%
“…To prevent tissue damage owing to hypoxaemia or hyperoxia, oxygenation of preterm infants needs to be monitored closely (1). Although there are multiple parameters influencing oxygenation, one of the leading parameters for the assessment of oxygenation is the ‘oxygen saturation measured by pulse oximetry (SpO 2 )’ (2). When oxygenation of preterm infants is controlled manually by the nursing staff, SpO 2 is frequently outside the target range (3–5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practice with respect to ventilator management, administration of oxygen, and assessment of oxygenation differs greatly among neonatal intensive care units (NICUs) [1,2]. Ventilator treatment exposes newborns to both hyperoxemia and hyperventilation.…”
Section: Introductionmentioning
confidence: 99%